Typical intracranial myiasis in Nigerian red river hogs (Potamochoerus porcus) caused by an unknown bot fly (Diptera: Oestridae). (April 2022) - Friant, Sagan; Young, Daniel K.; Goldberg, Tony L.
Abstract: We report an unknown taxon of bot fly (Diptera: Oestridae: Oestrinae) in red river hogs ( Potamochoerus porcus Linnaeus, 1758) in Cross River State, Nigeria. From direct observation and interviews with local hunters, we document that, remarkably, the parasite typically occurs within the intracranial supra-meningeal space – i.e., between the inner wall of the skull and the brain – but without causing visible inflammation or clinical signs. The parasite is most similar (up to 87.9%) to Rhinoestrus usbekistanicus based on cytochrome oxidase subunit 1 DNA sequencing but is sufficiently divergent phylogenetically to represent a new or previously un-sequenced taxon. Morphologically, the parasite shares some, but not all, features with R. nivarleti . Local cultural belief systems attribute aspects of red river hog behavior (e.g. intelligence, elusiveness) to the parasite, suggesting a prolonged presence in the red river hog population. The parasite's unusual anatomic location may be aberrant, or it may be a protective adaptation to life in red river hogs, which forage vigorously with their snouts. Graphical abstract: Image 1 Highlights: Bot flies of the family Oestridae threaten animal health, human health, and agriculture. This study describes an oestrid bot fly parasitizing wild red river hogs in Nigeria. The parasite is morphologically and genetically distinct but is well known among local hunters, who believe it confers intelligence and elusiveness to red river hogs. Remarkably, the new parasite typically infects the space between the brain and the interior of the skull of red river hogs, but without obvious illness. Results expand the known diversity and natural history of bot flies and call attention to species that could emerge in domestic animals and people.